In Vitro Antitumor Effect of Oils Rich in CBD and THC Cannabis Extract in Canine Prostate Carcinoma Cell Lines - Calheiros, Luís Gustavo Ramos de Moraes [UNESP]; Pedro, Giovana [UNESP]; Oliveira da Silva, Thayna [UNESP]; Amorim, Rogério Martins [UNESP]; Alves, Carlos Eduardo Fonseca [UNESP]; Laufer-Amorim, Renée [UNESP] (MDPI, 2024)
Prostate cancer is one of the leading causes of cancer-related deaths worldwide, even when diagnosed at an early stage in humans and dogs. Dogs have a significant incidence of spontaneous prostate cancer, which is highly similar to human androgen-independent prostate cancer and represents a valuable model for comparative studies. Cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC) are the two main cannabinoids extracted from Cannabis sativa and have demonstrated antiproliferative and anti-invasive properties in different tumor types. In this study, CBD or THC-rich extracts inhibited the proliferation of two canine prostatic carcinoma cell lines, PC1 and PC2, showing an IC50 of 3.43 and 3.57 μM for CBD rich extracts, and 4.90 and 4.48 μM THC rich extracts, respectively. Cell death was also observed with both Annexin V and Propidium iodide staining for the canine cell lines. These results provide new information concerning the use of rich oil in canine PC and open a promising opportunity for further in vitro and in vivo studies to establish the mechanisms of action of these compounds using dogs as a natural model for prostatic carcinoma.
Keywords: comparative oncology; medicinal plants; natural compounds; translational medicine